The First Few Hundred Cases for Coronavirus Disease 2019 (COVID-19) in Colombia - Julián Felipe PORRAS-VILLAMIL; Mario Javier OLIVERA; Nadia Katherine RÍOS-CAMARGO (Tehran University of Medical Sciences, 2020)
Background: SARS-CoV-2 virus is the causative agent of COVID-19 disease. It is essential to understand the epidemiological characteristics of the first few cases in each country. This study aimed to describe the geographical distribution, and temporal appearance of the first few hundred cases in Colombia. Methods: This observational study was conducted to review the literature and key documentary information from public health institutions, websites and news reports were examined. Results: The first few 100 cases for COVID-19 were confirmed in Colombia. According to sex, men with 54% predominate, the most affected age group was 20 to 29 yr old (26%), 9% of the cases required hospitalization and no deaths were reported. Most of the confirmed subjects were from the departments of Cundinamarca. To date, most cases are imported (63%), especially from Spain. Conclusion: The COVID-19 pandemic puts in evidence the lack of understanding, prevention and contention power of the different countries around the world is not as good as it could be. Politics must not affect the different proposed measures.